2006
DOI: 10.1182/blood-2006-07-036640
|View full text |Cite
|
Sign up to set email alerts
|

Commonly dysregulated genes in murine APL cells

Abstract: To identify genes that are commonly dysregulated in a murine model of acute promyelocytic leukemia (APL), we first defined gene expression patterns during normal murine myeloid development; serial gene expression profiling studies were performed with primary murine hematopoietic progenitors that were induced to undergo myeloid maturation in vitro with G-CSF. Many genes were reproducibly expressed in restricted developmental "windows," suggesting a structured hierarchy of expression that is relevant for the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…In brief, bone marrow aspirates were obtained from patients that gave informed consent. RNA was prepared from the unfractionated snap-frozen cell pellets and profiled using the Affymetrix Human Genome U133 Plus 2.0 Array GeneChip microarrays (Affymetrix) at the Siteman Cancer Center Molecular and Genomic Analysis Core Facility (38).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, bone marrow aspirates were obtained from patients that gave informed consent. RNA was prepared from the unfractionated snap-frozen cell pellets and profiled using the Affymetrix Human Genome U133 Plus 2.0 Array GeneChip microarrays (Affymetrix) at the Siteman Cancer Center Molecular and Genomic Analysis Core Facility (38).…”
Section: Methodsmentioning
confidence: 99%
“…22 We previously reported that leukemic blasts can be identified by the abnormal coexpression of the myeloid surface antigen Gr-1 and the early hematopoietic marker CD34 ( Figure 1A). 22,27,28 These Gr-1 ϩ CD34 ϩ APL cells partially retain the ability to terminally differentiate toward mature granulocytes and can be adoptively transferred to secondary recipients, which develop an identical, rapidly fatal leukemia within 2 to 3 weeks (dose and tumor dependent) after tumor inoculation. 22,[27][28][29] Finally, as shown in Figure 1A, Gr-1 ϩ CD34 ϩ blast cells express cell-surface CXCR4, with increased expression observed on cells obtained from the peripheral blood compared with the spleen and bone marrow.…”
Section: In Vivo Bioluminescence Imaging Of Aml Cell Traffickingmentioning
confidence: 99%
“…Of note, since Gr-1 ϩ CD34 ϩ APL cells partially retain the ability to terminally differentiate toward mature granulocytes, the majority of circulating baseline and mobilized cells in the leukemic mice shown in Figure 3C through E are mature granulocytes derived from the APL blast population. 22,27,28 We next evaluated whether repetitive daily injections of AMD3100 could remobilize normal hematopoietic progenitors and APL cells into the circulation. In these studies, B6129F1 mice were injected with 10 6 mCG PR/ϩ APL cells and administered a single dose of AMD3100 for 5 consecutive days 12 days after mCG PR/ϩ APL injection.…”
Section: Mobilization Of Apl Blasts By Amd3100mentioning
confidence: 99%
“…Affymetrix Expression Console software was used to process array images, export signal data, and evaluate image and data quality relative to standard Affymetrix quality-control metrics. 35 These data have been deposited into a public database (Gene Expression Omnibus: GSE23291).…”
Section: Expression Array Profilingmentioning
confidence: 99%